Pitiose cutânea equina de localização atípica tratada topicamente com solução de anfotericina B e DMSO - Dias, Deborah Penteado Martins [UNESP]; Dória, Renata Gebara Sampaio; Pereira, Rodrigo Norberto; Canola, Paulo Aléscio; Di Filippo, Paula Alessandra (My University, 2012)
Background: Cutaneous lesions by Pythium insidiosum infection are commonly observed in horses, especially in those living at flooded environments. Equine pythiosis is characterized by the development of tumoral masses that are frequently located at distal limbs, ventral abdômen, thorax, breast and face. The lesions are usually granulomatous, serosanguineous and ulcerated, most often destroyed by self-mutilation due to the intense pruritus. The proposed treatment includes surgical excision followed by antifungal drugs administration, which can be done systemically or topically. Amphotericin B and dimethyl sulfoxide (DMSO) in association has been successfully used for cutaneous pythiosis topical treatment due to the DMSO property to carry any substance through plasmatic membranes. Case: The present report concerns a 12-year-old mixed breed gelding presenting with self-mutilation of a tumoral mass located at the left flank. The owners reported that the horse had initially presented a small wound that had evolved to a 20-cm in diameter mass in 4 weeks. Tissue samples were collected, processed and stained by the Gomori's methenamine silver (GMS) method. The histopathological analysis revealed Pythium insidiosum hyphae in a granulomatous tissue, especially located at peripheral region, where kunkers were present. Surgical excision of the mass followed by cauterization was indicated as initial treatment, and due to financial reasons, the owners elected only the topical antifungal therapy to control the fungus infection after surgery. Flunixin meglumine was also administrated for five days aiming the control of pain and inflammation. The wound was cleaned with povidone-iodine solution and rinsed with a solution containing 50 mg of amphotericin B in 10 mL of sterile water and 10 mL of DMSO. This procedure was carried out twice a day. The wound healed fast due to an excellent centripetal epithelialization, and the horse was discharged after 64 days showing only 5% of the initial wound area. The owner reported by telephone the complete healing and hair growth 10 days after discharge. Discussion: Despite the atypical location of the tumoral lesion described at the present report, the history and clinical manifestations, especially the intense pruritus, showed similarity with other characteristic reports of equine cutaneous pythiosis. The diagnosis was confirmed by the histopathological examination showing hyphae structures, as described to be evidences of the presence of Pythium insidiosum in the tissue. The surgical procedure was the first step to provide remission of clinical signs, and one day after surgery the pruritus desapeared. After excision of the granulomatous tissue and cauterization, daily topical administration of amphotericin B associated with DMSO was effective in destroying the infectious agent, as observed by the excellent epithelization. A pink granulation tissue grew up providing an ideal surface for epithelial migration and the healing process progressed quickly. Centripetal epithelialization reduced the wound area until 3% of the initial area in 64 days of treatment, when the remaining wound was found almost completely healed and covered with hair. At the present report, the horse presenting pythiosis was only topically treated. The recommended therapy using amphotericin B and DMSO solution was effective, economically viable and low risk, considering that the systemic antifungal therapy usually suggested is expensive and extremely nephrotoxic. The atypical location of the lesion on the left flank shows that any anatomical region can be affected by the fungus, since the conditions for its development were present.
Topical treatment using Amphotericin B and DMSO for an atypically located equine cutaneous pythiosis
Keywords: Amphotericin B; Dimethyl sulfoxide; Flank; Horse; Pythiosis